Nilai – Nilai Dalam Tradisi Notok Ompong Perkawinan Adat Dayak Ransa Di Desa Nusa Poring Kecamatan Menukung Kabupaten Melawi - Mikaria, Mikaria; Bahari, Yohanes; Shilmy; Zakso, Amrazi; Sastra Atmaja, Thomy (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
This study aims to describe the values contained in the Notok Ompong tradition of marriage ceremonies within the Dayak Ransa indigenous community in Nusa Poring Village, Menukung District, Melawi Regency, West Kalimantan. Notok Ompong is a tradition for welcoming guests within the Dayak Ransa community. This research is a qualitative descriptive study involving research subjects such as the Tumenggung (customary leader), village head, customary officials, community leaders, and the general public. Data collection techniques used were observation, interviews, and documentation. Data analysis techniques included data reduction, data display, and conclusion drawing. The results of this study indicate that Notok Ompong is a tradition to welcome guests entering the bride's residence or those visiting the village for the first time. The values embedded in the Notok Ompong marriage tradition of the Dayak Ransa include religious values, mutual cooperation (gotong-royong), social values, solidarity, and local wisdom. Furthermore, the factors influencing the shift in values within the Notok Ompong tradition are social, temporal, and economic factors. Despite these influencing factors, the community continues to maintain and preserve the Notok Ompong tradition in Dayak Ransa traditional marriages in Nusa Poring Village, Menukung District, Melawi Regency